Evaluasi Penyelenggaran Madrasah Tsanawiyah Satu Atap (MTS-SA) Sabilul Muttaqien Pamekasan Jawa Timur - Munawiroh Munawiroh (Badan Litbang dan Diklat Kementerian Agama RI, 2013)
This article is a result of evaluative research of the implementation of Madrasah Tsanawiyah Satu Atap (MTs SA) Sabilul Muttaqien Pamekasan in Madura. The research is focused on how the development of education access on its school, the service availability, the service affordability, the student development and madrasah management. The method used in this research is evaluation method with qualitative approach. The research result concludes that the main facilities of the madrasah are available sufficiently, only the education means which not sufficient enough. On the madrasah management, it is also sufficed both in terms of educators and education personnel in accordance with the needs and academic qualifications as well as thier competencies. From management point of view, this madrasah has already had plans of activity programs, priority scales and five yearly programs. The mechanism of activity program implementations has been arranged on their organization structures and duties, as well as the scheduled evaluation for the activities. To guarantee the transparency and communityâ€™ involvement, those programs are arranged with involving the stakeholders element.Â Artikel ini merupakan hasil penelitian evaluatif tentang Penyelenggaran Madrasah Tsanawiyah Satu Atap (MTs SA), Kasus pada Madrasah Tsanawiyah Satu Atap (MTs SA) Sabilul Muttaqien Pamekasan di Madura. Penelitiannya difokuskan pada bagaimana pengembangan akses pendidikan pada sekolah tersebut, meliputi ketersediaan layanan, keterjangkauan layanan, perkembangan siswa dan tata kelola madrasah. Metode yang digunakan dalam penelitian ini yaitu metode evaluasi dengan pendekatan kualitatif. Hasil penelitian menyimpulkan bahwa sarana utama madrasah sudah tersedia dengan cukup memadai, hanya sarana pendidikan yang belum memadai. Begitu pula untuk pengelolalaan madrasah sudah terpenuhi baik tenaga pendidik maupun tenaga kependidikan sesuai kebutuhan dan sesuai kualifikadsi akademik dan kompetensinya. Dari segi manajemen, madrasah ini sudah memiliki perencanaan program kegiatan, skala prioritas dan program kegiatan jangka lima tahunan. Untuk mekanisme penyelenggaraan program kegiatan telah disusun struktur organisasi dan uraian tugasnya, serta evaluasi kegiatan terjadwal. Untuk menjamin transparansi dan keterlibatan masyarakat, program-program tersebut disusun dengan melibatkan unsur pemangku kepentingan (stakeholders).